2023
DOI: 10.1007/s12264-022-01013-6
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Microglia-based Therapeutic Approaches to Neurodegenerative Disorders

Abstract: As prominent immune cells in the central nervous system, microglia constantly monitor the environment and provide neuronal protection, which are important functions for maintaining brain homeostasis. In the diseased brain, microglia are crucial mediators of neuroinflammation that regulates a broad spectrum of cellular responses. In this review, we summarize current knowledge on the multifunctional contributions of microglia to homeostasis and their involvement in neurodegeneration. We further provide a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Microglia are closely related to the cognitive impairment and pathology of AD [ 46 , 47 ]. To investigate the potential mechanism of CARS-induced memory impairment, we examined the effects of neuronal CARS overexpression on microglia in the hippocampus of the C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
“…Microglia are closely related to the cognitive impairment and pathology of AD [ 46 , 47 ]. To investigate the potential mechanism of CARS-induced memory impairment, we examined the effects of neuronal CARS overexpression on microglia in the hippocampus of the C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has primarily focused on investigating the involvement of immune cells, particularly microglia, the resident macrophages of the CNS, in the pathogenesis of AD. Numerous studies have extensively examined and confirmed the characteristics of aging microglia ( 26 ), their role in the development of AD ( 27 ), and the effectiveness of interventions targeting aging microglia ( 28 ). However, it is important to recognize that AD is systemically influenced by both central and peripheral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies verified this therapeutic effect of Mr BMT in an AD mouse model (87, 88), demonstrating the clinical potential of microglia replacement. It also provides new and clinically feasible strategies for treating other neurological disorders (18, 85, 86, 89). Despite sharing similar characteristics with naïve microglia, Mr BMT cells are P2Y12 − (18).…”
Section: Discussionmentioning
confidence: 99%